SISTEM PEWARISAN KESENIAN RABAB PASISIE DI NAGARI ANAKAN KOTO NAN DUO KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Kens Fahta Aulia; Marzam Marzam; Yensharti Yensharti (FBS Universitas Negeri Padang, 2016)
This article aims to describe Art Inheritance Rabab Pasisie System In Nagari Anakan Koto Nan Duo Kecamatan Batang Kapas Kabupaten Pesisir Selatan.The method used is qualitative, which aims to get everything related to the topic. The data related to the topic above is collected through library research, observation, interview and documentation techniques.From the research results can be concluded that Art Inheritance Rabab Pasisie System in Nagari Anakan Koto Nan Duo Kecamatan Batang Kapas Kabupaten Pesisir Selatan, inherited enculturation. Where, man as a creature of reason, has the power of reflection and intelligence, learn to understand and adapt the mindset, knowledge and culture bunch of other human beings. The process of enculturation is the process of learning the culture through the study of socio-cultural norms and patterns of action in social interactions in order to belong to his personal and attitudes formed in temperament